Esthetic perception of the anteroposterior position of upper incisors in relation to the forehead - Marco Antonio Sánchez Tito; Luis Fernández García (Editorial Ciencias Médicas, 2020)
Introduction: Orthodontic treatment is mainly aimed at achieving stable occlusal relationships and enhancing the smile expression. The position of the upper central incisors plays a particularly important role in such an expression, and extracranial references have been suggested for its proper three-dimensional position. Awareness of the preferences of the various social actors involved may be useful to make appropriate decisions when planning the treatments. Objective: Evaluate the esthetic perception that orthodontists, dental surgeons and laypeople have of the smile with the upper central incisor in anteroposterior position with respect to the forehead and in lateral norm. Methods: A lateral norm photograph was used of a Peruvian woman with a normal profile and ideal anteroposterior position of the upper central incisor according to element II of Andrews' orofacial harmony. The photograph was digitally modified to obtain images with retruding (- 4 mm) and protruding (+ 4 mm) incisors. The photographs were evaluated by a panel composed of orthodontists, dental surgeons and laypeople. The evaluation was based on a visual analog scale. Results: The photograph with normal position of the upper central incisor with respect to the GALL line was ranked higher by orthodontists (67.658 ± 22.094) and laypeople (54.038 ± 20.524). To dental surgeons the protruded position was nicer (60.804 ± 3.626). Significant differences were found between the groups of evaluators and the photographs (p < 0.05). Conclusions: The esthetic appraisal of orthodontists was closer to the norm for anteroposterior position of incisors. The anteroposterior position of incisors plays an important role in the esthetic perception of the smile in the lateral norm.